Mechanical behavior of zirconium diboride–silicon carbide–boron carbide ceramics up to 2200 °C. Issue 2 (February 2015) - Neuman, Eric W.; Hilmas, Gregory E.; Fahrenholtz, William G.
Abstract The mechanical properties of hot pressed zirconium diboride–silicon carbide–boron carbide (ZrB2–SiC–B4C) ceramics were characterized from room temperature up to 2200 °C in an argon atmosphere. The average ZrB2 grain size was 3.0 μm. The SiC particles segregated into clusters, and the largest clusters were >30 μm in diameter. The room temperature flexural strength was 700 MPa, decreasing to 540 MPa at 1800 °C and to 260 MPa at 2200 °C. The strength was controlled by the SiC cluster size up to 1800 °C. At higher temperatures, strength was controlled by formation of liquid phases, and precipitation of large BN and B–O–C–N inclusions. The mechanical behavior of these materials changes at ∼1800 °C, meaning that extrapolation of properties from lower temperatures is not accurate. Mechanical behavior in the ultra-high temperature regime was dominated by impurities and changes in microstructure. Therefore, the use of higher purity materials could lead to significant improvements in ultra-high temperature strength.